The Enclosure and Alienation of Academic Publishing: Lessons for the Professoriate - Wilhelm Peekhaus (tripleC: Communication, Capitalism & Critique)
This paper interrogates and situates theoretically from a Marxist perspective various aspects and tensions that inhere in the contemporary academic publishing environment. The focus of the article is on journal publishing. The paper examines both the expanding capitalist control of the academic publishing industry and some of the efforts being made by those seeking to resist and subvert the capitalist model of academic publishing. The paper employs the concepts of primitive accumulation and alienation as a theoretical register for apprehending contemporary erosions of the knowledge commons through the enclosure effects that follow in the wake of capitalist control of academic publishing. Part of my purpose with this discussion will be to advance the case that despite a relatively privileged position vis-à-vis other workers, academic cognitive labourers are caught up within and subject to the constraining and exploitative practices of capitalist production processes.